PENGEMBANGAN BUKU AJAR BAHASA ARAB BERBASIS GAMBAR BERWARNA UNTUK MENINGKATKAN KEMAMPUAN BERBICARA SISWA MADRASAH IBTIDAIYYAH BAHRUL ULUM TAMBAKBERAS JOMBANG - Dini Sirma Budi; Aufia Aisa; Rina Dian Rahmawati (LPPM Universitas KH. A. Wahab Hasbullah, 2020)
This study aims to develop color picture-based Arabic textbooks to improve speaking skills in grade 2 madrasah ibtidaiyyah and measure the validity and effectiveness of the textbooks developed. This research is a research and development (RnD) using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Data collection techniques are carried out by distributing questionnaires and tests to 20 children. The results showed the acquisition of media validation test results was 88% and from material experts 83.75% can be categorized as very valid and can be used without revision. The results of trials conducted to determine the practicality of the product were obtained from the pre-test value of 57.65% and the post-test of 71%. The results of trials conducted to determine the effectiveness of the product obtained from the student questionnaire scores showed 84% results. It can be concluded that the developed textbook is achieved.